PENGARUH TRANSVERSE FRICTION TERHADAP SKALA NYERI PADA KASUS TENNIS ELBOW DI RSU SEMBIRING DELI TUA - Rudianto Rudianto; Simson Sinuhaji (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2018)
Data were obtained from Sembiring Deli Tua Hospital in Medan indicates that the number of patients with tennis elbow in January – June 2015 as many as 30 people suffering from tennis elbow on the elbow as a result of uncontrolled movement that lead to pain in the elbow area. The purpose of this study was to determine the effect of the transverse friction due to tennis elbow pain scale of the Elisabeth Hospital in Medan. This type of research is descriptive with the entire patient population that numbered 30 people tennis elbow, samples 23 people, the received data is primary data obtained directly from the respondents. Data were analyzed descriptively by looking at the percentage of the collected data. From the result of this study showed that in the entire sample frequency distribution of respondents by sex that many have tennis elbow is the female gender with a number of 15 people (65.2%), while the distribution of the samples by age that many have tennis elbow is the age of 30-35 years old (43.5%), while the distribution of the samples based on the job that many have tennis elbow is a housewife with a number of 10 people (43.5%).Based on this study it can be concluded that there is the influence of transverse friction in patients with tennis elbow.